Perceptions of Contractors and Consultants Toward Application of Greenship Rating Tools on Apartment Buildings in Surabaya - Herry Pintardi Chandra; Paulus Nugraha (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2014)
During the last ten years, the growth of apartment buildings in Surabaya has encountered the bitter experience of global warming, resource depletion, energy scarcity, and other environmental impacts. We cannot avoid them, but we can minimize the negative impacts of global warming. The green building concept is one of the methods to minimize the environmental impact. It takes into account principles of sustainable development in planning, construction, operation, and maintenance. Greenship Rating Tools is used to evaluate and calculate green achievements, prior to green building certification. The aim of this research is to represent the perceptions of contractors and consultants toward application of Greenship Rating Tools on apartment buildings in Surabaya. Based on the data obtained from a questionnaires survey carried out to 41 respondents, the mean value ranking method is used to evaluate the main factors of Greenship. These factors are Appropriate Site Development, Energy Efficiency and Conservation, Water Conservation, Material Resource and Cycle, Indoor Health and Comfort, and Building Environmental Management. In general, the results of this research show that there are a number of differences between perceptions of contractors and consultants toward application of Greenship Rating Tools on apartment buildings in Surabaya. According to the contractors’ perception, Visual Comfort is a factor that would easily to be applied, whilst consultants’ is Landscape. On the other hand, there are factors that would difficult to be applied. Based on contractors’ perceptiom is Climate Change, while consultants’ perception is Renewal Energy. In summary, Greenship Rating Tools can be applied on contractors’ and consultants’ perceptions, whilst there are some variables which can not be applied.